History and the Unconscious The Theoretical Assumptions and Research Practices of Psychohistory - Pawelec, Tomasz (Studies in History, Memory and Politics, 2021)
This work represents the first truly comprehensive and non-biased history of psychohistory, a vanguard branch of historical scholarship that studies the psychological dimension of the past using principles of psychoanalysis and psychology as its theoretical ground. Tomasz Pawelec is an experienced methodologist and historiographer who systematically examines, reconstructs, and evaluates the major theoretical and methodological guiding assumptions shared by psychohistorians. In effect, he provides the reader with an intriguing portrait of a peculiar research paradigm - and a specific intellectual "monad" - that developed within the twentieth-century American history. At the empirical foundation of his work lies a broad collection of psychohistorical publications.